SEQUENCING OF FUNGAL PATHOGEN ERYSIPHE POLYGONI DC CAUSING POWDERY MILDEW OF BLACK GRAM (Journal of Plant Disease Sciences, 2017)
Black gram ( (L.) Hepper) is the third most important pulse Vigna mungo crop in India. Powdery mildew caused by DC is one of the major Erysiphe polygoni constraints in the production of black gram causing both qualitative and quantitative loss of grains. The fungus has very wide host range spread by air borne and oidia also produces the sexual fruiting bodies cleistothecia and difficult to differentiate the species morphologically. Present study was carried out through DNA extraction followed by Polymerase chain reaction and Agarose gel electrophoresis and through ITS rDNA Sequencing. Molecular characterization has been done through amplification of ITS1 and ITS4 region and DNA sequencing. Dharwad isolate was proved to be after blasting the gene sequences in NCBI BLAST Erysiphe polygoni programme and it had 97% homology with Mexico isolate, whereas, it was similar up to 93% with Iran isolate. Present study also approves that rDNA-ITS sequences is the best method to identify the strains.
Keywords: Black gram , Powdery mildew , Molecular characterization Erysiphe polygoni